Biogeochemical behaviour of geogenic As in a confined aquifer of the Sologne region, France. (October 2022) - Battaglia-Brunet, Fabienne; Naveau, Aude; Cary, Lise; Bueno, Maïté; Briais, Justine; Charron, Mickael; Joulian, Catherine; Thouin, Hugues
Abstract: Arsenic (As) is one of the main toxic elements of geogenic origin that impact groundwater quality and human health worldwide. In some groundwater wells of the Sologne region (Val de Loire, France), drilled in a confined aquifer, As concentrations exceed the European drinking water standard (10 μg L −1 ). The monitoring of one of these drinking water wells showed As concentrations in the range 20–25 μg L −1 . The presence of dissolved iron (Fe), low oxygen concentration and traces of ammonium indicated reducing conditions. The δ 34 SSO4 was anticorrelated with sulphate concentration. Drilling allowed to collect detrital material corresponding to a Miocene floodplain and crevasse splay with preserved plant debris. The level that contained the highest total As concentration was a silty-sandy clay containing 26.9 mg kg −1 As. The influence of alternating redox conditions on the behaviour of As was studied by incubating this material with site groundwater, in biotic or inhibited bacterial activities conditions, without synthetic organic nutrient supply, in presence of H2 during the reducing periods. The development of both AsV-reducing and AsIII-oxidising microorganisms in biotic conditions was evidenced. At the end of the reducing periods, total As concentration strongly increased in biotic conditions. The microflora influenced As speciation, released Fe and consumed nitrate and sulphate in the water phase. Microbial communities observed in groundwater samples strongly differed from those obtained at the end of the incubation experiment, this result being potentially related to influence of the sediment compartment and to different physico-chemical conditions. However, both included major Operating Taxonomic Units (OTU) potentially involved in Fe and S biogeocycles. Methanogens emerged in the incubated sediment presenting the highest solubilised As and Fe. Results support the hypothesis of in-situ As mobilisation and speciation mediated by active biogeochemical processes. Graphical abstract: Image 1 Highlights: Arsenic of sedimentary origin influences quality of a French groundwater. Temporal variations of As- and S- cycles bio-indicators are observed on site. Incubations of core material show biologically related As solubilisation. Incubated core slurries and groundwater present distinct bacterial communities. As concentration and speciation is driven by bacterial activities.